How Social Practice Experiences Shape College Students’ Employability: Evidence from a Case Study in Chongqing, China - Li, Weiguang; Tubagus Achmad Darodjat (International Journal of Multidisciplinary Research, 2026)
This study examines how social practice experience shapes the employability of college students through a qualitative case study conducted in Chongqing, China. Although practical education has been widely promoted, existing research often indicates whether practice is beneficial rather than explaining how it helps improve employability. This study proposes a three mechanism framework consisting of human capital development, identity and psychological resource formation, and social capital accumulation, guided by the perspectives of experiential learning and graduate capital. The interview evidence explained in conjunction with publicly available employment indicators suggests that when students engage in real tasks, receive feedback, reflect on career expectations, and gain access to employment related networks, their employability becomes apparent. The research findings indicate that practice serves as both a learning environment and an opportunity interface, linking higher education with labor market access. This study contributes to the study of employability by providing mechanism oriented explanations based on non coastal Chinese backgrounds, and provides insights for higher education management, including structured reflection, employment quality assurance, and practice design based on partnershipss.